Effectiveness of Range of Motion (ROM) Fingers and Spherical grip to Extremity Strength in Non Hemorrhagic Stroke Patients - Hapsari, Shindi; Sonhaji, Sonhaji; Nurulia, Nindya (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This research is an experimental study with the design of the control group. The sampling technique is purposive sampling. The study's population was 32. The intervention group (n=16) respondents were given ROM therapy exercises of fingers and spherical grip, control group (n=16) respondents by giving ROM therapy exercise fingers. Exercise is done 2 times a day and done in 3 days for 15-20 minutes each time. Data analysis using Shapiro-Wilk, dependent paired t-test, and independent t-test. Statistical analysis results obtained by the intervention group (Range Of Motion therapy exercises (ROM) of the fingers of the hand and spherical grip exerted a more effective influence compared to the administration of therapy on the control group (ROM) of the fingers of the hand) get an average difference in extremity muscle strength with a p-value of 0.000